Docosahexaenoic acid (DHA) and arachidonic acid (ARA) balance in developmental outcomes. (June 2017) - Colombo, John; Jill Shaddy, D.; Kerling, Elizabeth H.; Gustafson, Kathleen M.; Carlson, Susan E.
Abstract: The DHA Intake and Measurement of Neural Development (DIAMOND) trial represents one of only a few studies of the long-term dose-response effects of LCPUFA-supplemented formula feeding during infancy. The trial contrasted the effects of four formulations: 0.00% docosahexaenoic acid (DHA)/0.00% arachidonic acid (ARA), 0.32% DHA/0.64% ARA, 0.64% DHA/0.64% ARA, and 0.96% DHA/0.64% ARA against a control condition (0.00% DHA/0.00% ARA). The results of this trial have been published elsewhere, and show improved cognitive outcomes for infants fed supplemented formulas, but a common finding among many of the outcomes show a reduction of benefit for the highest DHA dose (i.e., 0.96%DHA/0.64% ARA, that is, a DHA: ARA ratio 1.5:1.0). The current paper gathers and summarizes the evidence for the reduction of benefit at this dose, and in an attempt to account for this reduced benefit, presents for the first time data from infants' red blood cell (RBC) assays taken at 4 and 12 months of age. Those assays indicate that blood DHA levels generally rose with increased DHA supplementation, although those levels tended to plateau as the DHA-supplemented level exceeded 0.64%. Perhaps more importantly, ARA levels showed a strong inverted-U function in response to increased DHA supplementation; indeed, infants assigned to the formula with the highest dose of DHA (and highest DHA/ARA ratio) showed a reduction in blood ARA relative to more intermediate DHA doses. This finding raises the possibility that reduced ARA may be responsible for the reduction in benefit on cognitive outcomes seen at this dose. The findings implicate the DHA/ARA balance as an important variable in the contribution of LCPUFAs to cognitive and behavioral development in infancy. Highlights: Current infant formulas provide DHA and ARA. Our results support a DHA: ARA ratio of 1:1 or 1:2. A DHA intake exceeding ARA intake reduced benefit in some cognitive measures. Declining RBC ARA implicates dietary DHA/ARA balance in cognitive outcomes